2022
DOI: 10.3390/ma15030718
|View full text |Cite
|
Sign up to set email alerts
|

The Characterization of Fatigue Damage of 316L Stainless Steel Parts Formed by Selective Laser Melting with Harmonic Generation Technique

Abstract: Fatigue damage is the main reason for the failure of parts formed by selective laser melting (SLM) technology. This paper presents a high-order, harmonic, and nonlinear ultrasonic testing system for monitoring the generation and evolution of fatigue damage in SLM 316L stainless steel parts. The results demonstrate that the normalized ultrasonic, nonlinear coefficients show a significant dependence on the degree of fatigue damage of the tested specimen and that the normalized, ultrasonic, and nonlinear coeffici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 40 publications
(42 reference statements)
0
5
0
Order By: Relevance
“…Therefore, the ultrasonic nonlinear response of the complex dislocation structure in the fatigue process needs to be further explored. Qiao et al [ 51 ] carried out intermittent fatigue loading tests on 316L stainless steel specimens formed by Selective Laser Melting (SLM) and evaluated their fatigue damage using higher harmonic technology. The nonlinear ultrasonic testing system used in the test is shown in Figure 9 .…”
Section: Application Of Nonlinear Ultrasonic Testing Technologymentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, the ultrasonic nonlinear response of the complex dislocation structure in the fatigue process needs to be further explored. Qiao et al [ 51 ] carried out intermittent fatigue loading tests on 316L stainless steel specimens formed by Selective Laser Melting (SLM) and evaluated their fatigue damage using higher harmonic technology. The nonlinear ultrasonic testing system used in the test is shown in Figure 9 .…”
Section: Application Of Nonlinear Ultrasonic Testing Technologymentioning
confidence: 99%
“… TEM photos of fatigue specimen under different cycles [ 51 ]. ( a ) Dislocation line (10,000 times); ( b ) Dislocation tangle (20,000 times); ( c ) Dislocation vein (30,000 times); ( d ) Dislocation wall (40,000 times).…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…Selective laser melting (SLM) [1,2] is a promising rapid prototyping technology that can be used to fabricate any complex structural part with a molding density of nearly 100%. In the past decade, its application has expanded from the original conceptual mold design to the aerospace, biomedical, and automotive fields.…”
Section: Introductionmentioning
confidence: 99%
“…In the literature, this technique has been considered a potential non-destructive evaluation method for the study of the degradation phenomena in structures and components subject Metals 2024, 14, 11 2 of 17 to variable loads [18,19]. Moreover, studies on nonlinear techniques have shown that the first fatigue damage in metals is closely related to the nonlinear effects of ultrasound waves [20][21][22][23]. The ultrasound wave is substantially distorted during the propagation in the material such that it generates components of harmonics with a frequency greater than the fundamental, in which the amplitudes of the components of these harmonics depend on the elastic nonlinearity of the material.…”
Section: Introductionmentioning
confidence: 99%